2008
DOI: 10.1254/jphs.fp0071206
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Smilacis chinae Rhizome on NMDA-Induced Neurotoxicity In Vitro and Focal Cerebral Ischemia In Vivo

Abstract: Abstract. Previous work has shown that the Smilacis chinae rhizome (SCR) markedly inhibits amyloid β protein (25-35)-induced neuronal cell damage in cultured rat cortical neurons. The present study was conducted to further verify the neuroprotective effect of SCR on excitotoxic and cerebral ischemic injury using both in vitro and in vivo studies. Exposure of cultured cortical neurons to 1 mM N-methyl-D-aspartate (NMDA) for 12 h induced neuronal cell death. SCR (10 and 50 µg / ml) inhibited NMDA-induced neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 50 publications
(55 reference statements)
4
50
0
Order By: Relevance
“…Furthermore, some studies support that trans-Res inhibites the postsynaptic Glu receptors in hippocampal neurons, with NMDA receptors being more sensitive than AMPA receptors [17], which probably have an antioxidant effect that ameliorates ischemic brain injury. Res also inhibited NMDA-induced neuronal death, intracellular calcium increase and reactive oxygen species generation in rat cortical neurons, confirming the neuroprotective effect of Res [11,28]. However, other studies have shown that pretreatment with Res did not alter the magnitude of the hypothalamus-pituitary-adrenal axis response to NMDA [29].…”
Section: Res-mediated Neuroprotective Effects Against Glu-induced Excsupporting
confidence: 57%
“…Furthermore, some studies support that trans-Res inhibites the postsynaptic Glu receptors in hippocampal neurons, with NMDA receptors being more sensitive than AMPA receptors [17], which probably have an antioxidant effect that ameliorates ischemic brain injury. Res also inhibited NMDA-induced neuronal death, intracellular calcium increase and reactive oxygen species generation in rat cortical neurons, confirming the neuroprotective effect of Res [11,28]. However, other studies have shown that pretreatment with Res did not alter the magnitude of the hypothalamus-pituitary-adrenal axis response to NMDA [29].…”
Section: Res-mediated Neuroprotective Effects Against Glu-induced Excsupporting
confidence: 57%
“…Primary cortical neuron cultures were prepared using embryonic day 15 -16 Sprague-Dawley rat fetuses, as described previously (24,25). Neurotoxicity experiments were performed on neurons after 3 -4 days in culture.…”
Section: Induction Of Neurotoxicity In Primary Cultures Of Rat Cerebrmentioning
confidence: 99%
“…The final concentration of DMSO was ≤0.1%, which did not affect cell viability. For each experiment, A. cordata, oleanolic acid, N G -nitro-L-arginine methyl ester (L-NAME; Sigma), (5R,10S)-(+)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine (MK-801; RBI, Natick, MA, USA), and verapamil (Sigma) were applied 15 min prior to treatment with 10 μM Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). They were also present in the medium during Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) incubation.…”
Section: Induction Of Neurotoxicity In Primary Cultures Of Rat Cerebrmentioning
confidence: 99%
See 2 more Smart Citations